Educação ambiental na estruturação de mundos possíveis: o caso do Núcleo Córrego João Gomes CardosoMG - Daniela Campolina Vieira (2014)
The research was based on the actor-network theory theoretical and the exploration of possible worlds to analyze the actions among them the environmental education performed by a group of people who compose the Núcleo João Gomes Cardoso (NJGC). This fluid group has as its main objective the improvement of the quality of life, and it is consensual among its members that this improvement is linked to environmental quality. The NJCG performs its actions on the territory of the João Gomes Cardoso basin river, which is located in the municipality of Contagem, Minas Gerais. The research was divided in six stages: 1st Documents search and organization; 2nd Documentary analysis and categorization; 3rd Semistructured interview; 4th Inventory of actors; 5th Exploration of performed and possible worlds; and 6th Comparative analysis of the performance of NJGC and evidences of transformative EA, promoter of participatory water management. Six years of operation of the group were analyzed through registers in minutes, documents and photos, and the projected future scenarios (possible worlds) as well as recorded the scenario experienced (worlds performed) by the group and its modifications were identified. Based on the possible and performed worlds, actions of environmental education were identified and inferences were made about its potential to assist in the structuring of participatory water management in the watershed in question. This research considered the analysis of the performative environmental education, which does not pre-conceives the EA, but analyzes the actions who perform an environmental education that is guided as transformative by promoting changes, and not as a training, since it is accomplished by paths that are constructed by the group, based on the possible worlds that they envision, as well as the worlds performed that they experience. It is expected that the research might assist in the analysis of educational processes involving groups that perform actions on behalf of environmental improvements, contributing to the planning and execution of educational activities that can promote change and contribute to the formation of a common possible world in which quality of life is a premise for all.